Efl Students’ Perceptions Toward Watching Vlog Experience For Speaking Skill - sanjaya, Yunita; Ikhsan, M Khairi; Autila, Rani (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study has investigated EFL Students’ perceptions toward watching vlog experience for speaking skill. The focus of the research is to know student’s perceptions watching vlog for learning English in speaking skill including the advantages of watching Vlog and limitations from watching Vlog experience for speaking skill faced by them. The research was conducted at University PGRI Sumatera Barat. A qualitative method was employed to gather in-depth insights from the participants. The research involved semi-structured interviews with three EFL students from English Department from University of PGRI Sumatera Barat. The participants were selected based on their interest in watching vlogs for language learning and their willingness to share their experiences. Based on the findings of the interview data, watching vlogs experience for speaking skill was effective because has many advantages compared to disadvantages. Students perception towards watching vlog experience show that students has positive cognitive impression because all of the participants have been learning English since middle school, indicating a long term commitment to learning the language for improving their speaking skills. They reported that vlogs helped them improve their pronunciation, grammar, vocabulary, and fluency. The participants also appreciated the real-life scenarios and authentic language used in vlogs, which helped them learn the type of English used in daily lives. This study is significant because its findings can be used to inform the development/ self learning for EFL students that might enchance their speaking skills in English language learning.